Sustain, Adapt, and Overcome—Hypoxia Associated Changes in the Progression of Lymphatic Neoplasia - Matolay, Orsolya; Méhes, Gábor (Frontiers in Oncology, 2019)
Irregular perfusion and related tissue hypoxia is a common feature of solid tumors the role of which in the survival and progression cancer has been gradually recognized. Adaptation and selection mechanisms in hypoxic areas in solid tumors are regulated by Hypoxia Inducible transcriptional factor 1 (HIF1) and other hypoxia mediators and are associated with aggressive clinical behavior in a large spectrum of malignancies. Aggressive forms of lymphatic neoplasias present with solid tumor-like features, also including rapid cell growth, necrosis and angiogenesis, the clinical potential of which is still underestimated. While the role of regional hypoxia in normal B-cell maturation and malignant transformation is becoming evident, the impact of tissue hypoxia on their behavior is not well-understood. Compared to some of the common solid cancer types data for some of the key regulators, such as HIF1 and HIF2, and for their downstream effectors are available in a limited fashion. In the current review we aim to overview the physiological aspects of major hypoxia pathways during B-cell maturation and adaptation-related changes reported in lymphatic neoplasia covering important targets, such as carbonic anhydrases IX and XII (CAIX, CAXII), glucose transporter 1 (GLUT-1) and vascular endothelial growth factor (VEGF). In conclusion, experimental and clinical results direct to important but currently unexploited role of hypoxia-driven resistance mechanisms especially in aggressive forms of B-cell neoplasia.